Warriors of the storm : a novel - Cornwell, Bernard (Cornwell, Bernard. Last kingdom., 2016)
A fragile peace reigns in Wessex, Mercia and East Anglia. King Alfred's son Edward and formidable daughter, Aethelflaed, rule the kingdoms. But all around the restless Northmen, eyeing the rich lands and wealthy churches, are mounting raids. Uhtred of Bebbanburg, the kingdoms' greatest warrior, controls northern Mercia from the strongly fortified city of Chester. But forces are gathering against him.